Hydrodynamic modelling for Mondego estuary water quality management - Duarte, António A. L. Sampaio (2002)
The south arm of Mondego estuary, located in the central western Atlantic coast of Portugal, is almost silted up in the upstream area. So, tides, wind and the tributary river Pranto discharges mostly drive the water circulation in this system. Annual fresh water inflow, regulated by precipitation and by sluice management practices, has a significant impact on flow velocity, salinity, N:P ratios and light extinction coefficients, which interaction controls biomass growth and loss processes. Eutrophication has been taking place in this ecosystem during last twelve years, where macroalgae reach a luxuriant development covering a significant area of the intertidal muddy flat. A sampling program was carried out from June 1993 to January 1997. Available data on River Pranto flow discharges, salinity profiles, precipitation and nutrients loading into the south arm were used in order to get a better understanding of the ongoing changes. Since hydrodynamics strongly affects the occurrence of macroalgal blooms, residence time can be a key parameter to characterise this influence. Integral formulations are typically based on assumptions of steady state and well-mixed systems and thus cannot take into account the space and time variability of estuarine residence times, due to river discharge flow, tidal coefficients, discharge(s) location and time of release during the tidal cycle. This work presents the hydrodynamic modelling (1D and 2D-H) of this system in order to estimate some kinetic variables and the residence times variability to assess the main factors that control opportunistic macroalgal blooms, contributing to better environmental management strategies selection.